The impact of social insurance on health among middle-aged and older adults in rural China: a longitudinal study using a three-wave nationwide survey - Xinxin Ma; Takashi Oshio (BMC, 2020)
Abstract Background Many studies have examined the impact of social insurance on health, but the results have generally been mixed, presumably because they have not fully addressed potential biases related to the study's cross-sectional design. In this study, we conducted a longitudinal analysis to investigate how participation in two social insurance programs in China-the New Rural Social Pension Insurance (NRSPI) and the New Rural Cooperative Medical Scheme (NRCMS)-was associated with health outcomes among middle-aged and older adults in rural China. Methods Using three-wave longitudinal data from the China Health and Retirement Longitudinal Study conducted in 2011, 2013, and 2015, we estimated the dynamic fixed-effects regression models to examine the association between participation in the NRCMS/NRSPI and six types of health outcomes. Results Participation in the NRSPI was positively associated with some health outcomes, but the associations were relatively modest and were observed only for some specific age and household income groups. Participation in NRCMS was not associated with any health outcomes. Conclusions The results provide limited evidence of the positive impact of social insurance on health among middle-aged and older adults in rural China. Thus, social insurance programs should be reformed to enhance their positive impact on health.